2009
DOI: 10.1021/jf903612h
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of βN-Alkanoyl-5-hydroxytryptamides in Coffee by Means of LC-MS/MS-SIDA and Assessment of Their Gastric Acid Secretion Potential Using the HGT-1 Cell Assay

Abstract: A straightforward stable isotope dilution analysis (SIDA) for the reliable quantitative determination of (beta)N-C(18:0)- to (beta)N-C(24:0)-alkanoyl-5-hydroxytryptamides (C5HTs) in coffee powder and beverages by means of LC-MS/MS was developed. The developed SIDA showing accuracy values of 92.6-107% and precision between 0.5 and 7% relative standard deviation for the individual derivatives allowed the sensitive and selective quantification of the target compounds in coffee beverages. Depending on the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 16 publications
(49 reference statements)
1
23
1
Order By: Relevance
“…Experiments with biomimetic combinations as well as omission experiments revealed that N-MP and CA partially compensated the pro-secretory effect of other pro-secretory compounds. These results are in accordance with the previous findings of our group [7,9,11,24], which also demonstrated that the pro-secretory activity of C5HT depends on the number of carbons in the C-chain of the corresponding fatty acid [10]. Furthermore, the effect of CAFF on gastric acid secretion has been often described as pro-secretory [3,8,25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Experiments with biomimetic combinations as well as omission experiments revealed that N-MP and CA partially compensated the pro-secretory effect of other pro-secretory compounds. These results are in accordance with the previous findings of our group [7,9,11,24], which also demonstrated that the pro-secretory activity of C5HT depends on the number of carbons in the C-chain of the corresponding fatty acid [10]. Furthermore, the effect of CAFF on gastric acid secretion has been often described as pro-secretory [3,8,25].…”
Section: Discussionsupporting
confidence: 93%
“…Our previous results have shown that one coffee component, N ‐methylpyridinium (N‐MP), down‐regulated proton secretion in human parietal gastric tumor cells (HGT‐1) , when applied in combination with a lyophilized regular coffee beverage. In contrast, we also found that other coffee components such as CAFF as well as C5HT stimulated proton secretion in HGT‐1 cells when applied in coffee representative concentrations .…”
Section: Introductioncontrasting
confidence: 59%
“…administration of a coffee beverage containing high amounts of C5HTs induced ulcer formation, whereas no ulcers were detected in rats that received a steam-treated, C5HTs-depleted coffee beverage [3]. The pivotal role of C5HTs in stimulating gastric acid secretion was confirmed in previous studies of our own group, using, first, an activity-guided approach [8,9] and, second, a multiparametric approach [10] in human gastric tumor cells (HGT-1 cells). Treatment of HGT-1 cells with C5HTs in coffee representative concentrations not only induced proton secretion, but also induced the expression of prosecretory genes, for example, those encoding for the H + ,K + -ATPase alpha-subunit or the acetylcholine receptor CHRM3, and prosecretory EGFr signaling pathways.…”
mentioning
confidence: 74%
“…However, in this first approach, we were not able to identify which of the coffee components affect mechanisms of proton secretion. In a following approach, we were able to identify different N-alkanoyl-5-hydroxytryptamides as potent stimulators of proton secretion in HGT-1 cells depending on their alkanoylic substitution (28). However, other coffee constituents may have an effect on stomach acid secretion as well.…”
Section: Secretory Activity Of Solvent Fractions Prepared From Regularmentioning
confidence: 99%